On the Macroeconomic and Social Impact of the Coronavirus Pandemic in Latin America and the Developing World - Christian R. Proaño (Intereconomics)
Abstract While the COVID-19 pandemic posits a significant challenge to all societies around the world, it also reveals in the most dramatic manner the many abysmal differences between so-called advanced economies and the developing world.